1999
DOI: 10.1034/j.1399-3054.1999.105119.x
|View full text |Cite
|
Sign up to set email alerts
|

Coffee seeds contain 11S storage proteins

Abstract: A legumin‐like seed protein was purified from the endosperm of coffee (Coffea arabica L. cv. Colombia). In contrast to legumes, where efficient storage globulin extraction requires buffered saline solutions well above the acidic pKI of the globulins, coffee legumin is readily extracted with acidic aqueous buffers. The coffee legumin migrates like other 11S storage globulins in sucrose gradients. Subunits of coffee legumin have an apparent molecular mass of about 55 kDa after one‐dimensional SDS‐polyacrylamide … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
27
0
2

Year Published

2000
2000
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(33 citation statements)
references
References 34 publications
4
27
0
2
Order By: Relevance
“…For other nitrogenous compounds, such as caffeine, there is no proof of its significance as a nitrogen storage molecule in coffee (Baumann and Gabriel, 1984;Suzuki and Waller, 1986;Mazzafera, 1990). SDS-PAGE profile of proteins of coffee seeds showed the two main bands previously observed by other authors (Bade and Stegemann, 1982;Luthe, 1992;Ludwig et al, 1995;Acuña et al, 1999). During germination there was a decrease of these bands indicating that they were hydrolyzed.…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…For other nitrogenous compounds, such as caffeine, there is no proof of its significance as a nitrogen storage molecule in coffee (Baumann and Gabriel, 1984;Suzuki and Waller, 1986;Mazzafera, 1990). SDS-PAGE profile of proteins of coffee seeds showed the two main bands previously observed by other authors (Bade and Stegemann, 1982;Luthe, 1992;Ludwig et al, 1995;Acuña et al, 1999). During germination there was a decrease of these bands indicating that they were hydrolyzed.…”
Section: Discussionsupporting
confidence: 52%
“…Two main bands were also observed in SDS-PAGE gels. Recently, Acuña et al (1999) confirmed 11S proteins as the main storage proteins in coffee seeds. Most studies on coffee germination have dealt with preservation of the seed viability (Ellis et al, 1990) and to our knowledge, only two followed compositional changes during the process, in which the biological role of caffeine was investigated in germinating coffee seeds (Friedman and Waller, 1983;Baumann and Gabriel, 1984).…”
Section: Introductionmentioning
confidence: 99%
“…Comparison of amino acid sequences of 11S protein deduced from cloned full-length cDNAs reveals the existence of some differences that could not explain the variations of pI and of molecular weight usually observed by SDS-PAGE (Acuña et al, 1999;Baú et al, 2001) or 2D-gel electrophoresis (Rogers et al, 1999a). At the amino acid level, 11S storage proteins are relatively rich in glutamine, glycine, leucine and acid glutamic amino acid residues, respectively with 11 %, 10 %, 9 % and 7.5 % of total molecular weight.…”
Section: Evolution Of Proteins During Coffee Fruit Developmentmentioning
confidence: 99%
“…The origin of these variations is still unknown but could be due to the action of specific-proteases as described below. Because storage proteins seem to be encoded by a limited number of genes (Acuña et al, 1999;Lin et al, 2005), the analysis of 11S-cDNA sequences from different coffee species and cultivars should be interesting to provide an in depth view of their amino acid composition.…”
Section: Evolution Of Proteins During Coffee Fruit Developmentmentioning
confidence: 99%
“…This same subgroup contains some previously characterised genes, such as SH-EP (sulphydryl endoproteinase), which encodes a cysteine proteinase (Vm445927) that is involved in the degradation of storage globulin in germinating seeds and in the early development of ripening stage fruits in Vigna mungo (Yamauchi et al 1992). This fi nding is particularly interesting because the 11S globulin is the main storage protein in coffee seeds (Acuña et al 1999. The electrophoretic profi le of protein extracts shows that this storage protein is predominant in several cultivars and coffee species (Baú et al 2001).…”
Section: -Mcgmsamvsavvt----------------------------------------------mentioning
confidence: 97%